Interconnectedness of Libyan Financial and Real Sectors - Elgnaidi, Mohamed; Toprak, Metin; Toprak, Metin (Tolga Ulusoy, 2023)
The Global Financial Crisis of 2008 has motivated modern economists to investigate the link between economies as well as between real and financial sectors. Thus, in last decade the existence of real and financial connectedness has become a corner stone in policy making when understanding how financial shocks impact real economy (Uluceviz & Yılmaz, 2018). Therefore, the aim of this chapter is to analyse the interconnectedness between the real and financial sectors of Libya. To accomplish the chapter’s aim, firstly it discusses roles of real and financial sector. Secondly, this chapter shed light on a recent related empirical literature. Methods used in measuring the connectedness between financial and real sectors are drown thirdly. In the fourth section, this chapter illustrates the method used and the model for measuring the Libyan real and financial sectors dependency, in addition to variables selection. Fifthly, our empirical results are displayed. Finally, a conclusion will be highlighted.
Keywords: Interconnectedness; Libyan Real Sector; Libyan Financial Sector